Diagnostic Accuracy of Rectal Suction Biopsy for Hirschsprung Disease in a Thai Pediatric Setting - Jaema Mamimin; Anuwat Muanparai (Scientific Journal of Pediatrics, 2023)
Introduction: Hirschsprung disease (HSCR) necessitates early diagnosis to prevent complications. Rectal suction biopsy (RSB) offers a less invasive alternative to full-thickness biopsy. This study evaluates RSB's diagnostic accuracy in a Thai pediatric population. Methods: A retrospective review analyzed children suspected of HSCR who underwent RSB at a tertiary Thai hospital (2018-2024). RSB findings were compared to the gold standard (full-thickness biopsy or intraoperative findings). Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated. Results: 120 children (median age 2 months, range 1 day - 12 years) were included. RSB yielded 45 positive and 75 negative results. Gold standard confirmed 40 true positives, 5 false positives, 70 true negatives, and 5 false negatives. RSB's sensitivity was 88.9%, specificity 93.3%, PPV 88.9%, NPV 93.3%, and accuracy 91.7%. Conclusion: RSB demonstrates high diagnostic accuracy for HSCR in Thai children. It can serve as a valuable initial diagnostic tool, potentially reducing the need for full-thickness biopsies.